The spread of the Rose-ringed Parakeet, Psittacula krameri, in Turkey between 1975 and 2015 (Aves: Psittacidae). Issue 4 (2nd October 2018) - Per, Esra
Abstract : The Rose-ringed Parakeet ( Psittacula krameri ) was recorded in Turkey for the first time in 1975 and has since then established breeding populations in at least six cities as a consequence of intentional and accidental introductions. Parakeet sightings have been recorded in and around urban areas and records are available from 26 provinces. It is most abundant in İstanbul, followed by İzmir, Ankara, Yalova, Antalya, and Şanlıurfa. The distribution and population size has increased continuously especially since the mid-2000s. The population is estimated to be now over 1, 355 individuals in the country, which is still moderate compared to some other West European countries.